Foodborne Parasitic Diseases in Europe: Social Cost-Benefit Analyses of Interventions. Issue 11 (November 2018) - Robertson, Lucy J.; Torgerson, Paul R.; van der Giessen, Joke
Abstract : Social cost-benefit analysis (SCBA) can be used to evaluate the benefit to society as a whole of a particular intervention. Describing preliminary steps of an SCBA for two foodborne parasitic diseases, echinococcosis and cryptosporidiosis, indicates where data are needed in order to identify those interventions of greatest benefit.